Penerapan Model Pembelajaran Cooperative Tipe Jigsaw terhadap Kemampuan Menganalisis Unsur Intrinsik Puisi pada Siswa Kelas IV SD Swasta GKPS No 1 Pematang Siantar - Mery Chris Isabella Saragih; Rajainal Saragih; Romaida Karo-karo (Attractive : Innovative Education Journal, 2024)
The aim of this study was to determine whether there were significant differences in learning to analyze the intrinsic elements of poetry of students. This research was conducted in 2024 at SD GKPS no 1 Pematangsiantar. This is a quantitative research using an experimental approach and using the one group pretest-posttest model. Furthermore, this research will be compared with the related-test sample at the significant level or the 0.05 level (95%). The result is pre-test mean value = 62 and post-test mean value = 85.89. from the data analysis, the research hypothesis was tested using the “t” test. From thr research results obtained tcount =30.82 with a significant level of 0.05 (95% confidence level) with df 18 obtained t table: 2.0928. thus, if tcount > ttable, namely (30.82>2,0928) then Ho is rejected, With Ho rejection, Ha is accepted. It can be concluded that the result of the ability to to analyze the intrinsic elements of poetry of students for the IV of SD GKPS no 1 Pematang Siantar are better after using the Jigsaw Method.